REVIEW OF ESTIMATION OF POLLUTION LOAD TO LAKE VICTORIA - Cheruiyot, Charles; Muhandiki, Victor (European Scientific Journal, ESJ, 2014)
Lake Victoria is a shared East African transboundary freshwater lake. Its basin lies within Burundi, Kenya, Rwanda, Tanzania and Uganda. In the past, studies and projects done on Lake Victoria focused mostly within the lake but recently they have extended to the basin to facilitate holistic understanding. Estimation of pollution load has been with respect to total nitrogen, total phosphorous and biodegradable organic matter which are considered to be critical pollution parameters. This study reviewed methods used in the past studies to estimate pollution load to Lake Victoria to highlight shortcomings and possible ways of improvement. The baseline models used in the methods were elaborated with respect to their merits and demerits. Methods used in the studies vary and their outcomes are of the same order of magnitude but with notably significant differences with respect to some pollution load parameters. The variances are mainly attributed to methods and scarce data used. Alternative methods that would improve the quality of the output by incorporating technology advancements in Remote Sensing and Geographical Information Systems (GIS) were also considered. GIS based tools are one of the options to overcome challenges in describing spatially and temporally varying environmental attributes.